Levels of health literacy among people living with HIV in outpatient care: a cross-sectional study from Denmark - Lotte Ørneborg Rodkjaer; Merete Storgaard; Nanna Toxvig Sørensen; Liv Marit Valen Schougaard (AIDS Research and Therapy, 2023)
Abstract Background Low health literacy (HL) among people living with HIV (PLWHIV) encounter more disease related complications, more difficulty understanding health-related information and low adherence. Considering that, the HL levels among PLWHIV needs to be further investigated. The objective of this study was to investigate the levels of HL and patient involvement among PLWHIV in an outpatient clinic in Denmark. A second objective was to examine differences in HL levels across socio-demographic characteristics. Methods In 2019, a population of 682 PLWHIV from a Danish outpatient hospital clinic were enrolled in cross-sectional study. Patients who had a digital postbox received an electronic questionnaire including following domains; health literacy, patient involvement, and socio-demographic status. Health literacy was measured using the Health Literacy Questionnaire (HLQ) through scores on three subscales: social support for health (HLQ4), engaging with healthcare providers (HLQ6), and understanding health information (HLQ9). An unpaired t-test was used to investigate mean differences in the HLQ scores across socio-demographic variables. Results A total of 338 (55%) patients responded to the questionnaire. The included participants demonstrated high levels of HLQ4 (mean = 4.2) and HLQ6 (mean = 4.2), but lower for HLQ9 (mean = 2.9). In total 70–80% reported being involved in decisions about their health. We found a positive association between high level of HL (HLQ9) and living with a partner and higher levels of HL (HLQ4, HLQ6, and HLQ9) and employment. Conclusion PLWHIV in a Danish out-patient care population were found to have high levels of HL despite differences in demographic characteristics. Further research is needed to examine the levels of HL among non-responders to develop HL approaches and strategies to meet the needs of individuals with different HL skills.